1994
DOI: 10.1017/s0145553200016989
|View full text |Cite
|
Sign up to set email alerts
|

Personal Names and Cultural Change: A Study of the Naming Patterns of Italians and Jews in the United States in 1910

Abstract: Although individual and personal, names take on their significance in social interaction. Since the context of social interaction changes with immigration, names can be expected to change as well. In this paper, we use information from the Public Use Sample of the 1910 U.S. census to compare the patterns of personal (given) names of first- and second-generation Italian and Jewish immigrants and native-born whites of native parentage, and to examine the association of naming patterns of immigrants with several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Oftentimes, ethnic groups voluntarily give up their traditional first names and adopt names of the dominant ethnic group without state intervention. There are multiple examples of such voluntary acculturation processes (Weitman 1987;Watkins and London 1994). Jewish names had already been stigmatized in Germany long before the time of National Socialism.…”
mentioning
confidence: 99%
“…Oftentimes, ethnic groups voluntarily give up their traditional first names and adopt names of the dominant ethnic group without state intervention. There are multiple examples of such voluntary acculturation processes (Weitman 1987;Watkins and London 1994). Jewish names had already been stigmatized in Germany long before the time of National Socialism.…”
mentioning
confidence: 99%
“…In line with the findings of previous studies, we assume that immigrants more often choose names that are common in the host country for girls than for boys (Watkins and London 1994;Lieberson 2000;Sue and Telles 2007;Becker 2009). To explain this phenomenon, we investigate several factors that can be assigned to two broader explanatory dimensions: we assume that the parents' decision is shaped by (1) specific features of the context of origin and (2) immigrants' level of integration into the host society.…”
Section: Naming Practices and The Child's Gendermentioning
confidence: 82%
“…Various studies have tried to explain why some immigrants decide on boundary crossing, whereas others choose boundary maintenance. Results indicate that the likelihood of boundary crossing is larger, the smaller the cultural distance between home and host country and the better immigrants are integrated in the host society socially in terms of friendships or intermarriage and structurally in terms of education, occupation, and citizenship (Watkins and London 1994;Lieberson 2000;Gerhards and Hans 2009). 3 At the same time, some studies have identified gender differences in naming (Lieberson 2000;Sue and Telles 2007;Becker 2009): they all find that parents choose boundary crossing significantly more often for their daughters' first names, whereas they are more likely to stick to boundary maintenance when naming sons.…”
Section: Introductionmentioning
confidence: 98%
“…Sociologists of culture and migration have treated first names as indicators of ethnic belonging and cultural assimilation (Lieberson 2000;Watkins and London 1994). While choosing first names from the host society indicates a desire for assimilation among immigrant parents, giving names common in the homeland suggests ethnic maintenance.…”
Section: Naming Assimilation and Transnationalismmentioning
confidence: 99%